The Impact of Social Media Marketing and E-Wom on Purchase Decisions Through Purchase Intention: Study on Ready-to-Eat Food - Alyssa Anindya Putri; Mohamad Rizan; Ika Febrilia (LPPM Universitas Negeri Jakarta, 2022)
The focus of this research is to determine the influence of social media marketing on purchase intention, the influence of e-WoM on purchase intention, the influence of purchase intention on purchase decisions, the influence of social media marketing on purchasing decisions, the influence of e-WoM on purchase decisions, and the influence of social media marketing and e-WoM on purchasing decisions through a purchase intention. A questionnaire was used as the data collection instrument in a survey approach. The research sample included 250 people who follow Lokasaji on social media, live in Jabodetabek, are 17 and above, and have purchased Lokasaji products in the last six months. SPSS and LISREL's SEM (Structural Equation Model) were used for data analysis. The results of the hypothesis test show that all hypotheses are accepted.